Pengaruh Pelatihan, Pengembangan Kapasitas Dan Pemberian Reward Terhadap Peningkatan Kinerja Sumber Daya Manusia di Destinasi Kapalo Banda Taram Kabupaten Lima Puluh Kota - Susi Ramayanti; Yulihasri Yulihasri (FEB Universitas Maritim Semarang, 2022)
This study aims to examine the effect of training, capacity building, and reward provision on improving the performance of human resources at the Kapalo Destination of Banda Taram, Lima Puluh Kota Regency. This study used a questionnaire distributed in the Destination of Kapalo Banda Taram, Kabupaten Lima Puluh Kota as many 53 respondents using the Structural Equation Model (SEM) PLS data analysis technique. The results of this study indicate that Training and Rewards have a positive and significant effect on improving the performance of managers at the Kapalo Banda Taram Destination while the capacity building has no significant effect on improving performance at the Kapalo Banda Taram Destination. This research implies that the existence of training and rewards can make performance better, especially in the Destination of Kapalo Banda Taram, Regency of Lima Puluh Kota.